Changes in the Trophic Structure of the Vertebrate Predator Community in the Cold Season in Belarussian Paazerje (Northern Belarus) with Emphasis on Depopulation of the Wild Boar, Sus scrofa (Artiodactyla, Suida) - Ivanovskij, V.; Sidorovich , A.; Solovej , I. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2021)
Anthropogenic disturbances often alter patterns of community functioning. Along that, how interacting species respond to these changes remains poorly understood. In 1972-2019, we studied the trophic structure of the vertebrate predator community in coniferous-small-leaved forests of Belarussian Paazerje (Northern Belarus). Since 2013, large scale depopulation of wild boars Sus scrofa has been started in Belarus as a measure to reduce a circulation of the African swine fever (ASF). It was found that the community consisted of four trophic guilds including small rodent consumers, bird consumers, scavengers, and ungulate consumers. The pronounced shifts in dietary compositions of three scavengers (the raccoon dog Nyctereutes procyonoides, golden eagle Aquila chrysaetos and white-tailed eagle Haliaeetus albicilla) after a decrease in an abundance of wild boar carrion has been revealed. Along that, the average value of the dietary similarity between investigated species stayed the same